2022
DOI: 10.1093/jpp/rgac083
|View full text |Cite
|
Sign up to set email alerts
|

Antiovarian cancer mechanism of esculetin: inducing G0/G1 arrest and apoptosis via JAK2/STAT3 signalling pathway

Abstract: Objectives Esculetin is a coumarin derivative, which is extracted from the dried barks of fraxinus chinensis Roxb. Although it is reported esculetin possesses multiple pharmacological activities, its associated regulatory mechanism on ovarian cancer isn’t well investigated. Methods Cytotoxicity is evaluated by MTT, clonogenic and living/dead cells staining assays. Migration and invasion effects are investigated by wound heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Esc also delayed wound healing in these cells, indicating its migration-inhibitory properties. Transwell assays also demonstrated that Esc suppressed the migration and invasion of SKOV3 cells ( 35 , 37 ). Furthermore, flow cytometry and western blotting analysis revealed that Esc treatment decreased the expression of cyclin D1, CDK4, CDK2 and cyclin E, suggesting its role in regulating the cell cycle in SKOV3 and HeLa cells ( 35 ).…”
Section: In Vitro Anticancer Properties Of Escmentioning
confidence: 93%
See 2 more Smart Citations
“…Esc also delayed wound healing in these cells, indicating its migration-inhibitory properties. Transwell assays also demonstrated that Esc suppressed the migration and invasion of SKOV3 cells ( 35 , 37 ). Furthermore, flow cytometry and western blotting analysis revealed that Esc treatment decreased the expression of cyclin D1, CDK4, CDK2 and cyclin E, suggesting its role in regulating the cell cycle in SKOV3 and HeLa cells ( 35 ).…”
Section: In Vitro Anticancer Properties Of Escmentioning
confidence: 93%
“…Studies conducted by Yin et al ( 35 ), Jiang et al ( 36 ) and Yang et al ( 37 ) revealed that Esc inhibited the proliferation of SKOV3 ovarian cancer cells, Ishikawa and HEC-1B endometrial cancer cells, and HeLa cervical adenocarcinoma cells in a time- and dose-dependent manner, but Esc showed low cytotoxicity towards human L02 normal hepatocyte cells ( 35 ). In addition to inhibiting cell proliferation, a single cell colony formation assay showed that Esc exerted an inhibiting effect on the colony forming ability of SKOV3 ovarian cancer cells.…”
Section: In Vitro Anticancer Properties Of Escmentioning
confidence: 99%
See 1 more Smart Citation
“…82 Esculetin had shown to diminish cell viability and promote apoptosis via a G0/G1 cell cycle arrest characterized by increased ROS generation in both in vitro and in vivo studies. 83 In conclusion, esculetin has the potential to function as a therapeutic agent for the treatment of ovarian cancer by inhibiting cell growth and triggering apoptosis via the activation of caspases and the JAK2/STAT3 signaling pathway.…”
Section: Ovarian Cancermentioning
confidence: 97%
“…Esculetin induced apoptosis and inhibited cell proliferation in HO‐8910 cells in vitro by enhancing the expression of caspase‐3, ‐9, and Bax/Bcl‐2 82 . Esculetin had shown to diminish cell viability and promote apoptosis via a G0/G1 cell cycle arrest characterized by increased ROS generation in both in vitro and in vivo studies 83 …”
Section: Anticancer Activity Of Esculetin On Various Typesmentioning
confidence: 99%